Modeling long-term attainable soil organic carbon sequestration across the highlands of Ethiopia - Abegaz, Assefa; Ali, Ashenafi; Tamene, Lulseged; Abera, Wuletawu; Smith, Jo U. (Environment, development and sustainability, 2022)
The objectives of this study across the highlands of Ethiopia were: (i) to characterize the association between soil organic carbon (SOC) stocks and biophysical variables and (ii) to model and map attainable SOC sequestration associated with five improved land management practices. The spatial distribution of the SOC stock was studied using a multiple linear regression model driven by eight biophysical predictors. A widely used SOC model (RothC) was then used to model changes in SOC over the next 20–50 years of improved land management. Simulations were driven by the derived SOC stocks, pH and clay contents that are available in the ISRIC soils database at 250 m resolution and climate data from the “Enhancing National Climate Services Initiative” database. Organic carbon inputs to the model were estimated from the “Improved Crop Varieties Yield Register” of the Ministry of Agriculture and Livestock Resource and the Central Statistics Authority. After 50 years of conservation tillage with 80% of available manure applied to cultivated land, the total SOC stock increased by 169,182,174 t, which is 2.8 times higher than the stock increase with only 50% of available manure applied. Introduction of improved pasture species and measures to control soil erosion was an important source of net carbon sequestration in grasslands. Afforestation and reforestation of degraded landscapes and protection of natural ecosystems further increased soil carbon. This highlights the importance of improved land management practices to SOC sequestration, which in turn could enhance agricultural productivity, food security and sustainable development.